2012
DOI: 10.1038/mt.2011.213
|View full text |Cite
|
Sign up to set email alerts
|

AAV Transduction of Dopamine Neurons With Constitutively Active Rheb Protects From Neurodegeneration and Mediates Axon Regrowth

Abstract: There are currently no therapies that provide either protection or restoration of neuronal function for adult-onset neurodegenerative diseases such as Parkinson's disease (PD). Many clinical efforts to provide such benefits by infusion of neurotrophic factors have failed, in spite of robust effects in preclinical assessments. One important reason for these failures is the difficulty, due to diffusion limits, of providing these protein molecules in sufficient amounts to the intended cellular targets in the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
165
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(175 citation statements)
references
References 50 publications
(71 reference statements)
8
165
1
1
Order By: Relevance
“…Neurodegenerative movement disorders such as PD are the result of a progressive loss of neurons and axons in the CNS, leading to motor dysfunction Kim et al, 2012). Although the main cause of PD remains elusive, it is well known that CNS inflammation and immune activation play major roles in the pathophysiology of PD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurodegenerative movement disorders such as PD are the result of a progressive loss of neurons and axons in the CNS, leading to motor dysfunction Kim et al, 2012). Although the main cause of PD remains elusive, it is well known that CNS inflammation and immune activation play major roles in the pathophysiology of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous immunohistochemical studies have shown that numerous activated microglia, characterized by enlarged cell bodies with short processes, are present in the neurotoxin-treated SN of various animal models of PD Whitton, 2007;Kim et al, 2011) and in the SN of patients with PD (Hirsch et al, 1998). Furthermore, under neuropathological conditions, activated microglia produce a spectrum of potentially neurotoxic molecules, including reactive oxygen species, which contribute to the oxidative stress and death of DA neurons Block and Hong, 2005;Kim et al, 2010). Similar to microglial activation, reactive astrocytes could produce neurotoxic cytokines such as IL-1␤ and TNF-␣ in animal models of PD (Hunot et al, 1999;Yokoyama et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the fact that the adult mammalian central nervous system (CNS) is incapable of an axonal regenerative response after injury has been challenged by the recent work by Park et al showing that constitutive activation of Akt-mTORC1 signaling in adult retinal ganglion neurons prior to optic nerve injury promoted regeneration of their axons (Park et al, 2008;Kim et al, 2012). Irrevocably, Akt and Rheb play an important role in protection and regeneration of axons not only during the period of acute axon injury but also 3 weeks post-lesion, by which time the degenerative process has run its course and ceased (Kim et al, 2011(Kim et al, , 2012.…”
Section: Rheb In Neuroprotection and Axon Regenerationmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) and glial cell-derived neurotrophic factor (GDNF) are required for regulating the development, maintenance function and plasticity of mature neurons and hence are important in protection of neurons in Parkinson's diseases (PD), which is characterized by progressive degeneration of dopaminergic (DA) neurons (Kim et al, 2012;Jeon and Kim, 2015;Nam et al, 2015). Transduction of DA neurons with adenoassociated virus constructs containing a constitutively active form of Rheb (AAV-hRheb S16H), provided protection of DA neurons from 1-methyl-4-phenylpyridine (MPP) induced degeneration in adult brain.…”
Section: Rheb In Neuroprotection and Axon Regenerationmentioning
confidence: 99%